Survei Manajemen Guru Pendidikan Jasmani di Kecamatan Temanggung - Aji, Muhammat Styo; Qoriah, Anirotul (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study is to determine the management of planning (planning), organizing (organizing), directing (actuating), and controlling (controlling) Physical Education teachers to support the success of learning. This research is a descriptive research with a quantitative approach and survey research design. The population of this study were all physical education teachers from 36 elementary schools in Temanggung District. The sampling technique is saturated sampling technique (total sampling) so that the total research sample is 25 teachers. Data collection techniques used observations and questionnaires which were then analyzed quantitatively. The results showed that (1) The implementation of planning management (planning) for State Elementary School Physical Education teachers in Temaggung District to support learning success was classified as good criteria with an average of 76.4%. (2) The implementation of organizing management in the criteria is quite good with an average of 68.2%. (3) The implementation of organizing management in the criteria is quite good with an average of 68.6%. (4) The implementation of management supervision (controlling) in the criteria is quite good with an average of 66.4%. The conclusion of this study is that the management of physical education teachers at the State Elementary School of Temanggung District has been running quite well starting from planning, organizing, directing and supervising